A Cross Sectional Study on Adherence to Medication among Patients with Hypertension and/or Diabetes Attending One of the Tertiary Care Institutes of Ahmedabad City, Gujarat, India - Janak Patel; Kanal Shah; Jayveer Jain; Venu Shah (University Library System, University of Pittsburgh, 2024)
Background: The lifelong management of chronic diseases such as Hypertension and Diabetes Mellitus necessitates a comprehensive approach, including lifestyle modifications and consistent adherence to medication. Present study aimed to evaluate treatment adherence among patients with diabetes and /or hypertension attending a tertiary care institute in Ahmedabad city, India. Methods: A cross-sectional study was conducted among 200 patients aged over 18 years, diagnosed with diabetes and/or hypertension. The sample population was selected from a tertiary care institute at Ahmedabad city using a consecutive sampling method. Data collection utilized a pretested and predesigned proforma along with the Morisky Medication Adherence Scale (MMAS-8). Results: Hypertension was present in 43.0% of the participants, while 20.0% reported diabetes mellitus. Additionally, 37.0% had both conditions. Out of total 200 patients 53.5% exhibited low adherence to treatment. Lower adherence to treatment was found to be more among Diabetics (67.5%) as compared to hypertensive patients (51.2%). Among participants having comorbidities 48.6% had low adherence to treatment. The association between disease type and adherence levels was not significant (p-value = 0.305). Not having any symptoms and forgetfulness were common reasons for low adherence among 41.1% and 24.2% of participants, respectively. Conclusion: This study highlights the need for targeted interventions aimed at enhancing medication adherence among individuals managing with chronic illnesses like hypertension and diabetes. The findings provide valuable insights for healthcare professionals and policymakers to develop effective strategies for improving treatment adherence and subsequently mitigating the progression of these chronic conditions.